(untitled) - Anderson, Laurie Halse (New York, 2010)
Separated from his friend Isabel after their daring escape from slavery, fifteen-year-old Curzon serves as a free man in the Continental Army at Valley Forge until he and Isabel are thrown together again, as slaves once more.
Keywords: Pennsylvania,Pennsylvania; History,Lịch sử; Revolution, 1775-1783,Cách mạng, 1775-1783